2012
DOI: 10.1016/j.seares.2011.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in the seasonality of selected diatoms related to grazers and environmental conditions

Abstract: The decoupling of trophic interactions could be one of the severe consequences of climate warming in aquatic systems. The timing of phytoplankton blooms, in particular, can affect competition within the plankton community as well as food-web interactions with zooplankton and fish. Using long-term data from Helgoland Roads in the southern North Sea, we examine diatom seasonality, using three representative diatom species combined with environmental and copepod time series over the last four decades. The long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 46 publications
1
40
0
Order By: Relevance
“…From an ecological perspective, major questions persist concerning the factors that promote diatom bloom events and determine how long a bloom lasts. Schlüter et al (2012) have recorded 45 yr of G. delicatula blooms showing a predominantly summer bloom with decadal scale changes in duration and timing of onset; in our shorter time series, we also see some variation, but with a predominantly winter bloom. The nanoflagellate parasite of G. delicatula is recognizable throughout our data set during 2 of its presumed 3 life stages due to the distinct morphology within G. delicatula frustules during infection.…”
Section: Introductionsupporting
confidence: 44%
See 1 more Smart Citation
“…From an ecological perspective, major questions persist concerning the factors that promote diatom bloom events and determine how long a bloom lasts. Schlüter et al (2012) have recorded 45 yr of G. delicatula blooms showing a predominantly summer bloom with decadal scale changes in duration and timing of onset; in our shorter time series, we also see some variation, but with a predominantly winter bloom. The nanoflagellate parasite of G. delicatula is recognizable throughout our data set during 2 of its presumed 3 life stages due to the distinct morphology within G. delicatula frustules during infection.…”
Section: Introductionsupporting
confidence: 44%
“…While many species are present in the MVCO time series and blooms are typically multispecies events, G. delicatula represents one of the greatest contributors to phytoplankton biomass, which is also true in another temperate coastal time series (Schlüter et al 2012). From an ecological perspective, major questions persist concerning the factors that promote diatom bloom events and determine how long a bloom lasts.…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of dinoflagellates has increased in the Northeast Atlantic and in the North Sea as both temperature and seasonal stability in temperature have increased, whereas diatoms, which have higher diversity at intermediate and less seasonally stable temperatures, have shown less increase in diversity. Analysis of daily (work days) sampling of phytoplankton, nutrients and temperature at Helgoland Roads (54°11′ 3″N, 7°54′E) from 1962 to 2008 showed that the phenology of three diatom species Guinardia delicatula, Thalassionema nitzschioides and Odontella aurita did not respond to climate warming in the same way and that overwintering population size, grazing, nutrient levels and water clarity affected their bloom timing (Schlüter et al 2012). Such species-specific differences in sensitivity to forcing factors could lead to shifts in community structure with potentially far-reaching consequences for ecosystem dynamics.…”
Section: Climate and Changes In Phytoplankton Abundance And Phenologymentioning
confidence: 99%
“…trophic level) are sufficient to predict future outcomes or whether careful study of the individual species is required, however the differences in phenological responses between different diatom species indicates the latter (Schlüter et al 2012).…”
Section: Brief Synthesis and Reflection On Future Developmentmentioning
confidence: 99%
“…Information is available regarding seasonal succession patterns (Hagmeier and Bauerfeind, 1990;Reid et al, 1990), response to environmental factors (Freund et al, 2012;Gillbricht, 1988;Hickel, 1998;Schlüter et al, 2012), and biodiversity (Hoppenrath, 2004;Hoppenrath et al, 2007;Wiltshire and Dürselen, 2004). However, since most of this information is based on microscopic observation, it covers mainly the microphytoplankton (20-200 μm).…”
Section: Introductionmentioning
confidence: 99%